Influence of the magnetic field on particle dynamics in capillary discharge of the soft X-ray laser - Maslov, V.I.; Tretyakov, V.N.; Azarenkov, N.A.; Borisko, V.N.; Yegorov, A.M.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2005)
In this paper the possibility of increase of quantity of flashes of soft x-ray laser radiation due to application of a small external magnetic field during development of the capillary discharge is considered. Розглянута можливість збільшення кількості лазерних спалахів м'якого рентгенівського випромінювання, що встигають розвитися в капілярному розряді за час розряду, за рахунок застосування магнітного поля. Рассмотрена возможность увеличения количества лазерных вспышек мягкого рентгеновского излучения, которые успевают развиться в капиллярном разряде за время разряда, за счет применения магнитного поля.